Prognostic Significance of the Systemic Immune-Inflammation Index in Patients With Cholangiocarcinoma: A Meta-Analysis - Liu, Xue-chun; Jiang, Yue-ping; Sun, Xue-guo; Zhao, Jian-jian; Zhang, Ling-yun; Jing, Xue (Frontiers in Oncology, 2022)
Background The systemic immune-inflammation index (SII) is a significant prognostic factor for neoplastic diseases. However, the prognostic value of SII in patients with cholangiocarcinoma (CCA) remains unclear. This meta-analysis aimed to investigate the prognostic value of preoperative SII in patients with CCA. Method We systematically searched for relevant studies in PubMed, Scopus, EMBASE, Web of Science, PROSPERO, and Cochrane Library databases up to March 22, 2022. Hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the association between SII and survival outcomes, including overall survival (OS) and recurrence-free survival. Results Five studies with 1402 patients were included in this meta-analysis to determine the prognostic value of preoperative SII. The results showed that a higher SII was associated with poor OS in patients with CCA who underwent invasive surgery (HR=1.916; 95% CI, 1.566–2.343; Z=6.329; P<0.001). The results were reliable in the subgroup analysis according to country, age, sample size, SII cutoff values, and treatment methods. Conclusions A high preoperative SII appears to be an effective and practical method for monitoring survival in patients with CCA. Systematic Review Registration International Platform of Registered Systematic. Review and Meta-Analysis Protocols (INPLASY), identifier INPLASY202240015.